PERINTISAN USAHA ANEKA MAKANAN RINGAN BERBAHANDASAR PANGAN LOKAL SEBAGAI BENTUK RECOVERYPASCA ERUPSI MERAPI DI DESA ARGOMULYO - Rizqie Auliana, Fitri Rahmawati, Siti Hamidah, Kokom Komariah, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
tMain activities of the program Enterprises Various Planting MadeSnack Food Association Local Shape Recovery For Post-eruption of Merapiin Argomulyo Village have been prepared based on a survey that in manylocations available sweet potatoes. Community service objectives are: 1)Know and practice the development of snack food products from cassava,maize, beans, bananas, sweet potato so that it can be accepted by society atlarge. 2) Know and practice the use of oil centrifuge technology inimproving the quality of production. 3) Know and practice the use ofsuitable packaging is used in order to attract more consumers. 4) Know andapply the method of calculating break-even price and production of localfood processing. 5) Able to produce and market a variety of snack foodproducts made from local food.Skills training of local food processing has been successfullyimplemented properly for 3 times face to face training events in brief form,namely the stage of theory, practice stage and evaluation stage andmotivation. Theoretical material provided is a) Knowledge of materials, b)Packaging and labeling, c) Calculation of selling price and the BEP, and d)Food production. Theory of matter is given for 90 minutes. The materialprovided is the practice of processing: cassava flour, banana flour, maizeflour, cassava dumplings burst, mozzarella sticks cassava, cassava widaran,ceriping banana honey, bananas ceriping chocolate, nuts disco , nuts atoms,dent beans, corn tortillas, and sweet potato snack. This material is providedfor 360 minutes by dividing the participants into 5 groups.This training is successful because it has been in accordance withestablished indicators of success, namely the training declared a success if80% of participants until training is completed and verified the presence ofthe Presence, and 80% of participants have enough value in a test ofknowledge and skills that can be expressed creatively and food processinglocal food products into a variety of light at the time of display. Assessmentresults show the presence of 99% of participants came to attend trainingthrough to completion. While the evaluation practices (skills) has seen morethan 70% have good skills in the preparation, processing and presentation.25Perintisan Usaha Aneka Makanan Ringan Berbahan Dasar Pangan LokalWhile the attitude or response to these training activities 71% very helpfuland 29% useful.